Correlation and path analysis in Indian mustard (Brassica juncea (L.) Czern & Coss) grown under rainfed condition - Singh, D K Kardam, V V (Journal of Spices and Aromatic Crops, 2005)
The nature and magnitude of associations and path coefficients for 10 characters in 200 F, and F, progenies of Indian mustard (Bmssicn jllllecn) obtained from six crosses were studied at Jobner (Rajasthan). Phenotypic correlation coefficients were higher in magnitude compared to genotypic correlation coefficients for most of the traits. Seed yield plant" was significantly and positively correlated with plant height, primary branches plant" , number of siliquae plant", number of seeds siliqua" and lOOO-seed weight. Highest direct contribution to seed yield was by number of siliquae plant", followed by primary branches plant ", 1000-seed weight, number of siliquae on main shoot and number of seeds siliqua". Hence, these traits could form a good selection criteria for improvement of seed yield in Indian mustard.